Pendidikan Karakter Berbasis Nilai-Nilai Pesantren: Konstruksi Akhlakul Karimah di Era Disrupsi Digital - Luthfi; Ach. Abu Supyan; Sri Harmonika (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
The era of digital disruption presents complex challenges for character education, where moral values experience erosion due to massive and prolonged technology exposure. Pesantren as the oldest Islamic educational institution in Indonesia possesses a value system that has been tested in forming akhlakul karimah character through fundamental values: sincerity, simplicity, independence, Islamic brotherhood, and freedom. This conceptual article aims to construct a theoretical framework for pesantren values-based character education that is responsive to digital era challenges without losing its spiritual essence. Through conceptual analysis method with critical-hermeneutic approach, this study explores the internalization mechanisms of pesantren values in the context of digital disruption. The analysis reveals that pesantren values have strategic relevance as foundation for character formation in digital era through three mechanisms: first, pedagogical transformation that integrates digital technology with traditional pesantren learning methods without compromising moral values; second, revitalization of habituation system adapted to santri's digital life context; third, strengthening value ecosystem through hidden curriculum and role modeling. Recent research confirms that pesantren successfully integrating traditional values with digital innovation can produce graduates who are morally noble while technologically competent. Theoretical implications include reformulation of character education concept that is non-dichotomous between traditional values and modernity, development of Islamic ethics-based technology integration model, and construction of comprehensive character assessment. This article provides conceptual contribution to sustainable character education development in pesantren in the digital disruption era.